Mitochondrial Dynamics Related Genes -MFN1, MFN2 and DRP1 Polymorphisms are Associated with Risk of Lung Cancer - Liang X; Dang S (Dove Medical Press, 2021)
Xiaohua Liang,1 Shengqiang Dang2 1Department of Thoracic Surgery, Tangdu Hospital, The Fourth Military Medical University, Xi’an, Shaanxi, 710038, People’s Republic of China; 2Department of Oncology, Chang’an Hospital of Xi’an, Xi’an, Shaanxi, 710016, People’s Republic of ChinaCorrespondence: Shengqiang DangDepartment of Oncology, Chang’an Hospital of Xi’an, 17 Wenjing Road, Xi’an, Shaanxi, 710016, People’s Republic of ChinaEmail sqdangcah@163.comPurpose: This study aimed to evaluate the associations between mitochondrial dynamics related genes -MFN1, MFN2 and DRP1 polymorphisms and risk of lung cancer.Methods: Six polymorphisms of MFN1, MFN2 and DRP1 were genotyped in 600 cases and 600 controls using a MassARRAY platform.Results: The MFN1 rs13098637-C and DRP1 rs879255689-A alleles were associated with an increased risk of lung cancer (prs13098637=0.004, prs879255689=0.005), while MFN2 rs4240897-A and rs2236058-G were related to a decreased risk of disease (p< 0.001). The rs13098637-TC/CC and rs879255689-GA/AA were determined as risk genotypes for lung cancer (prs13098637=0.014, prs879255689=0.013), whereas the rs4240897-GA/AA and rs2236058-GG were identified as protective genotypes against lung cancer risk (p< 0.001). Genetic model analysis showed that rs13098637 was correlated with an elevated risk of lung cancer in dominant and log-additive models (pdominant=0.007, plog-additive=0.004). Moreover, rs879255689 was associated with an increased risk of disease in all three models (pdominant=0.014, precessive=0.028, plog-additive=0.005). In contrast, rs4240897 and rs2236058 were related to reduced risk of disease in all three models (rs4240897: pall< 0.001; rs2236058: pdominant=0.008, precessive< 0.001, plog-additive< 0.001). In addition, these associations were related to the smoking status and pathological type of lung cancer patients.Conclusion: These results shed new light on the association between mitochondrial dynamics related genes and risk of lung cancer.Keywords: lung cancer, gene polymorphisms, mitochondrial dynamics, MFN1, MFN2